Psychological Capital in Educators: The Role of Hope, Efficacy, and Resilience in Preventing Teacher Burnout - Miftahuddin Miftahuddin; Livia Alves; Thiago Rocha (Yayasan Adra Karima Hubbi, 2025)
Teacher burnout is a pervasive challenge in education, negatively affecting both educators’ well-being and student outcomes. Psychological capital, encompassing hope, self-efficacy, resilience, and optimism, has emerged as a critical protective factor against occupational stress. Understanding how specific components of psychological capital influence burnout can inform interventions aimed at promoting teacher well-being and sustaining instructional effectiveness. This study investigates the role of hope, self-efficacy, and resilience in preventing burnout among educators in primary and secondary schools. A quantitative research design was employed, involving 150 teachers selected through stratified random sampling. Participants completed standardized questionnaires measuring psychological capital dimensions and burnout levels. Statistical analyses, including correlation and multiple regression, were conducted to examine predictive relationships. Findings indicate that higher levels of hope, self-efficacy, and resilience are significantly associated with lower burnout scores. Among the components, self-efficacy exhibited the strongest protective effect, followed by resilience and hope. The study concludes that cultivating psychological capital is essential for mitigating teacher burnout, enhancing professional commitment, and promoting sustainable teaching practices.